Shy temperament in childhood: investigating the role of maternal mind-mindedness - Misailidi, Plousia; Orfanidou, Sofia (Psychology: the Journal of the Hellenic Psychological Society, 2021)
Relations between children’s temperamental shyness and mothers’ propensity to think and describe their children as individuals with minds (mind-mindedness) were examined. A between groups design was used to assess whether mothers of a group of 5- to 8-year-old shy children (n = 60) and mothers of a comparison group with non-shy children (n = 60) differed in the frequency and types of references they made to their children’s mental states. Mothers were asked to provide written descriptions of their children (Meins & Fernyhough, 2010, 2015). Descriptions were coded for references to three types of mental states: volitional (e.g. “want”, “need”, “try”), cognitive (e.g. “think”, “believe”) and emotional (e.g. “happy”, “sad”, “shy”). Shyness was assessed through separate parent and teacher reports of children’s temperament. As predicted, differences were found in the overall number of references to mental states, but also in the types of mental states to which mothers of shy and non-shy children referred. Temperamental shyness was associated with more frequent maternal references to children’s mental states and specifically to emotions. Findings are discussed in relation to the need to extend our understanding on the potential associations between child characteristics, such as temperament, and maternal mind-mindedness.